Across the copperbelt: urban and social change in Central Africa’s borderland communities - Larmer, M (James Currey, 2021)
The first comparative historical analysis - local, national and transnational - of the cross-border Central African copperbelt; a key work in studies of labour, urbanisation and African studies.